Video versus direct laryngoscopy to improve the success rate of nasotracheal intubations in the neonatal intensive care setting: a randomised controlled trial - Tippmann, Susanne; Schäfer, Janine; Winter, Julia; Mühler, Ann-Kathrin; Schmitz, Katharina; Schönfeld, Mascha; Eichinger, Michael; Mildenberger, Eva; Kidszun, André (BMJ paediatrics open, 2023)
Objective: To assess whether video laryngoscopy (VL) for tracheal intubation of neonates results in a higher first-attempt success rate and fewer adverse tracheal intubation-associated events (TIAEs) when compared with direct laryngoscopy (DL). - Design Single-centre, parallel group, randomised controlled trial. - Setting: University Medical Centre Mainz, Germany. - Patients: Neonates <440/7 weeks postmenstrual age in whom tracheal intubation was indicated either in the delivery room or in the neonatal intensive care unit. - Intervention: Intubation encounters were randomly assigned to either VL or DL at first attempt. - Primary outcome: First-attempt success rate during tracheal intubation. - Results: Of 121 intubation encounters assessed for eligibility, 32 (26.4%) were either not randomised (acute emergencies (n=9), clinicians’ preference for either VL (n=8) or DL (n=2)) or excluded from the analysis (declined parental consent (n=13)). Eighty-nine intubation encounters (41 in the VL and 48 in the DL group) in 63 patients were analysed. First-attempt success rate was 48.8% (20/41) in the VL group compared with 43.8% (21/48) in the DL group (OR 1.22, 95% CI 0.51 to 2.88).The frequency of adverse TIAEs was 43.9% (18/41) and 47.9% (23/48) in the VL and DL group, respectively (OR 0.85, 95% CI 0.37 to 1.97). Oesophageal intubation with concomitant desaturation never occurred in the VL group but in 18.8% (9/48) of intubation encounters in the DL group. - Conclusion: This study provides effect sizes for first-attempt success rates and frequency of TIAEs with VL compared with DL in the neonatal emergency setting. This study was underpowered to detect small but clinically important differences between the two techniques. The results of this study may be useful in planning future trials.
DOI funktioniert nicht
Online veröffentlicht: 10. Juli 2023
Gesehen am 31.10.2023